Audit of common errors in death certificates issued by tertiary care hospitals in Lahore - Maqsood, Muhammad; Zahid Bashir, Muhammad; Abaidullah, Muhammad (Journal of Fatima Jinnah Medical University, 2020)
Death certificate is the last legal document of one’s life. It provides not only valuable information about the deceased but also is a source of data required for devising national health related policies. So, this necessitates its completion according to the guidelines issued by World Health Organization (WHO).1 This study was aimed to determine the types and frequencies of errors during the completion of death certificates by the doctors at tertiary care hospitals of Lahore. Subjects and Methods: It was a retrospective study carried out at 3 tertiary care hospitals of Lahore during a period from Jan 2015 to June 2015. A total of 10359 death certificates of the patients who died during the said period and did not undergo autopsy were included in the study. Errors were abstracted and divided into 7 categories starting from category I to VII. Results: No death certificate was found error free. The highest number (97.4%) of the error was confusion between cause of death and mechanism/mode of death. It was followed by error in underlying cause of death accounting for 81.6% and then immediate cause of death 57.8%. Frequency of errors in the standard WHO recommended format was 49.95%. Conclusion: Most common error observed in this study was confusion of cause of death with mechanism/mode of death sufficient to misinterpret the cause. These errors may be attributed to lack of knowledge, training, and experience of the certifying doctors.